2018
DOI: 10.1177/0013916517752435
|View full text |Cite
|
Sign up to set email alerts
|

Do Social Norms Affect Support for Earthquake-Strengthening Legislation? Comparing the Effects of Descriptive and Injunctive Norms

Abstract: Social norms have been successfully applied in health promotion and environmental conservation, but their potential for encouraging natural hazard preparation is relatively untested. This research extends the focus theory of normative conduct to natural hazards and cognitive-behavioral outcomes by examining whether focusing individuals on descriptive and injunctive norms increases their support for earthquake-strengthening legislation in a seismically active city: Wellington, New Zealand. In a large community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 50 publications
(84 reference statements)
4
43
0
Order By: Relevance
“…Unfortunately, there is a lack of research into social norms in environmental hazards and earthquake preparedness writ large (Vinnell, Milfont, & McClure, 2019). However, some research indicates that social norms are used in hazard situations to make sense of mitigation and response activities.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there is a lack of research into social norms in environmental hazards and earthquake preparedness writ large (Vinnell, Milfont, & McClure, 2019). However, some research indicates that social norms are used in hazard situations to make sense of mitigation and response activities.…”
Section: Discussionmentioning
confidence: 99%
“…External nudging can appeal to individuals' internal norms highlighting their self‐negotiated standards. It can also lead consumers to follow injunctive norms when their decision‐making mechanisms are in contention with each other or when the desire to do something is lurking in the background (Mahon, Cowan, & McCarthy, 2006; Vinnell, Milfont, & McClure, 2019). This leads to hypothesis 5 (H5).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Even private disaster preparation can be influenced by social pressures. Some studies have already shown that descriptive norms play an essential role in disaster preparation (Kunreuther et al., 1978; Lo, 2013; Morsink & Geurts, 2012; Paek, Hilyard, Freimuth, Barge, & Mindlin, 2010; Vinnell, Milfont, & McClure, 2019).…”
Section: Social Norm Approaches On Disaster Risk Reductionmentioning
confidence: 99%